Sustainable Tourism through Coffee: Agrotourism Development in Turekisa Village, East Nusa Tenggara - Nono, Elfridus Andi Loke; Patiung, Markus; Sastryawanto, Hary (SCIENTIA: Journal of Multi Disciplinary Science, 2024)
Agrotourism in Indonesia stands as a vital potential for development support. Indonesia boasts numerous agrotourism destinations, with one such developed site located in Turekisa Village, Ngada Regency, East Nusa Tenggara (NTT). This tourist destination has gained prominence due to its breathtaking natural beauty, often dubbed as the "land above the clouds," a reputation that continues to grow alongside the increasing number of visitors to the hills and the abundant natural resources, particularly the substantial coffee production at Bukit Wolobobo. The coffee cultivated around Bukit Wolobobo is of the Arabica variety. The aim of this study is to analyze strengths, opportunities, weaknesses, and threats, and to determine development strategies for coffee-based agrotourism in Turekisa Village, Ngada Regency. The research methodology employs SWOT analysis, drawing data from interviews with six key informants: the Head of Agriculture Department, Head of Tourism Department, Agricultural Extension Officer, Chairperson of the Coffee Farmers' Group, Tourism Management, and Community Leaders. The findings of this study indicate placement in Quadrant I, suggesting that the coffee plantation agrotourism in Turekisa Village needs to be maintained and further enhanced given its significant quality potential.